2013
DOI: 10.12688/f1000research.2-55.v1
|View full text |Cite
|
Sign up to set email alerts
|

The rise of testicular germ cell tumours: the search for causes, risk factors and novel therapeutic targets

Abstract: Since the beginning of the 20th century there has been a decline in the reproductive vitality of men within the Western world. The declining sperm quantity and quality has been associated with increased overt disorders of sexual development including hypospadias, undescended testes and type II testicular germ cell tumours (TGCTs). The increase in TGCTs cannot be accounted for by genetic changes in the population. Therefore exposure to environmental toxicants appears to be a major contributor to the aetiology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 92 publications
(176 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, several additional susceptibility loci have been reported, including three that overlap with the locations of KITLG , SPRY4 and BAK1 , involved in KIT signaling pathways regulating proliferation, survival and migration of primordial germ cells or TGCT development. 14 …”
mentioning
confidence: 99%
“…Subsequently, several additional susceptibility loci have been reported, including three that overlap with the locations of KITLG , SPRY4 and BAK1 , involved in KIT signaling pathways regulating proliferation, survival and migration of primordial germ cells or TGCT development. 14 …”
mentioning
confidence: 99%
“…[ 101,102 ] Another finding suggested that the c‐Kit receptor promotes cell survival via activation of Akt‐mediated phosphorylation of Bad on Ser136. [ 103 ] However, the precise molecular mechanism by which Akt activation induces Oct3/4 or c‐Kit overexpression is yet to be investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Confounding this situation, three additional studies focusing on PFOA exposure and mortality from testicular cancer all failed to identify an association in occupationally exposed workers (87,96,97). Thus, whilst not universally demonstrated, the potential significance of these positive associations is highlighted by parallel correlations between the widespread increase in worldwide PFAS usage and the rising prevalence of testicular cancer; a pathology that has significantly increased in recent times to become the most common malignancy in young men aged 20-40 years (98)(99)(100)(101). Although the characterization of testicular cancer remains incomplete, there is speculation that environmental factors, as opposed to genetic factors, are a key contributor to the etiology of this form of cancer (98,102).…”
Section: Pfas Human Health Associationsmentioning
confidence: 99%